Market Potential and Regional Economic Growth in Spain, 1860-1930 - Rafael González-Val; Julio Martínez-Galarraga; Daniel A. Tirado-Fabregat (European Regional Science Association (ERSA), 2014)
In this paper we employ parametric and nonparametric techniques to analyse the effect of the changes registered on regional market potential on the growth of Spanish regions during the period 1860-1930. The study of the Spanish experience during these years conforms a case study that allows analyzing whether the construction of new transport infrastructure, as well as the changes in trade policy, that affected the relative market potential of the Spanish regions, ended up shaping regional growth trajectories. In order to carry out the analysis we make use of new evidence on regional inequality patterns in the long term based on recent estimations of per capita GDP for NUTS III Spanish regions (provinces) and an a la Harris measure of regional market potential that takes into account the economic distance between territories according to the changes registered in transport networks, the variations in the actual transport costs and the tariff policy followed over the period. Our results show a clear positive influence of market potential on regional economic growth, particularly along the years 1900-1930.
Keywords: R0; N9; O18; N64; F14; 330; market potential; New Economic Geography; regional growth; economic history